Morphogenesis of limph nodes in Muscovy ducks during early posnatal onthogenesis - Gavrilina, O.; Gavrilina, O. G.; Gavrylina, O.; Gavrylina, O. G.; Havrylina, O.; Havrylina, O. G.; Gavrilina, Olena; Gavrilina, E. G.; Гавриліна, Олена Геннадіївна; Perotskaya, L. V.; Пероцька, Людмила Вадимівна; Alekseeva, Nataliya; et al. (Alex Matsyura Press, 2020)
The dynamics of mass and linear parameters of lymph nodes of ducks is a direct reflection of structural and functional transformations of their lymphatic parenchyma. The peculiarities of quantitative dynamics of tissue components of peripheral lymphatic organs at early stages of postnatal ontogenesis are to a great extent determined by advanced growth rates of their absolute mass against the background of sharp increase of their antigenic stimulation intensity. Parenchyma of lymph nodes of newborn ducklings is characterized by relatively low degree of differentiation and is represented by diffuse lymphatic tissue with no pronounced signs of its division into separate functional zones. Internally, the lymphatic channel is represented by only two lymphatic sinuses - the central one, which is located in the central part of the organ and occupies a large relative area and a discrete edge sinus, which borders on the node capsule and has a much smaller relative area and, accordingly, is located at its periphery. The organ parenchyma is a diffuse cluster of stromal and lymphatic cells in the enlarged lymphatic vessel between the central (inner) and edge (outer) lymphatic sinuses, without signs of its division into cortical and brain matter. Among the lymphatic tissue of the lymph node, reticular stroma cells and the population of small lymphocytes have the largest relative amount. Динаміка маси та лінійних параметрів лімфатичних вузлів качок є прямим відображенням структурно-функціональних перетворень їх лімфатичної паренхіми. Особливості кількісної динаміки тканинних компонентів периферичних лімфатичних органів на ранніх стадіях постнатального онтогенезу значною мірою визначаються швидкими темпами зростання їх абсолютної маси на тлі різкого збільшення інтенсивності їх антигенної стимуляції. Паренхіма лімфатичних вузлів новонароджених каченят характеризується відносно низьким ступенем диференціації і представлена дифузною лімфатичною тканиною без яскраво виражених ознак її поділу на окремі функціональні зони. Внутрішньо лімфатичний канал представлений лише двома лімфатичними синусами - центральним, що розташований в центральній частині органу і займає велику відносну площу і дискретним крайовим синусом, який межує з капсулою вузла і має значно меншу відносну площу і, відповідно, розташований на її периферії. Паренхіма органу - це дифузне скупчення стромальних та лімфатичних клітин у збільшеній лімфатичній судині між центральною (внутрішньою) та крайньою (зовнішньою) лімфатичними пазухами без ознак її поділу на коркову та мозкову речовини. Серед лімфатичної тканини лімфатичного вузла найбільшу відносну кількість мають ретикулярні клітини строми та популяція дрібних лімфоцитів.
Морфогенез лімфатичних вузлів Мускусних качок на ранніх стадіях постнатального онтогенезу
Гавриліна Олена Геннадіївна http://orcid.org/0000-0001-9624-9510 Алексєєва Наталія Вікторівна https://orcid.org/0000-0003-1984-5209
Keywords: reticular stroma; ретикулярна строма; muscovy duck; мускусна качка; lymph node; лімфатичний вузол; parenchyma; паренхіма; lymphatic sinus; лімфатичний синус